Enzymatic Disruption of Biofilms During Cheese Manufacturing: A Mini Review - Kumar, Murali; Tierney, Joseph; Wilkinson, Martin (Frontiers in Microbiology, 2021)
Bacteria are capable of colonizing industrial processing surfaces creating biofilms on them which may adversely affect the quality and safety of products. Traditional cleaning-in-place (CIP) treatments using caustic and nitric acid solutions have been known to exhibit variable efficiency in eliminating biofilm bacteria. Here, we introduce enzymes as an alternative to traditional CIP treatments and discuss their mechanism of action against bacterial biofilms in cheese manufacturing. In addition, we discuss research gaps namely thermal stability, substrate specificity and residual activity of enzymes that may play a vital role in the selection of enzymes with optimal effectiveness against multi species biofilms. The outcome of this mini review will aid in the development of a novel and sustainable enzyme-based CIP treatment during cheese manufacturing in the future.